Digital Vitruvius, or an elogy of the equilateral triangle - Maggio, Francesco (DISEGNARECON, 2012)
On interpretation of an architectural project, triangle’s form generally refers both to plans of organic architecture and to fronts of Romanesque and Gothic churches. This wonderful form, that contains God’s eye, is, according to Vitruvius, the geometric generative principle of the Roman Theatre. Everybody knows that De Architectura arrived to us without images; in the past there were innumerable interpretations, from editio princeps (1486). A digital transcriptions, that follows side by side a Vitruvius’ book’s translation, highlights the compositional process that defines that the equilateral triangle is the geometric element that give origin to the composition of theatre.